2017
DOI: 10.1016/j.jcyt.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and proliferation of human mesenchymal stromal cells in the right ventricular myocardium after intracoronary injection in a large animal model of pulmonary hypertension

Abstract: Background aims In this study, we demonstrate long-term persistence of human mesenchymal stromal cells (hMSCs) after intracoronary injection in a large animal model of pulmonary hypertension (PH). Methods Commercially available placenta-derived hMSCs were used. Experiments were conducted on 14 female Yorkshire swine. Four animals served as controls, and 10 underwent pulmonary vein (PV) banding. After 12 ± 2 weeks, PH and PV dysfunction were confirmed by right heart catheterization and cardiac magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Pulmonary arterial hypertension (PAH) is a chronic and devastating disease in which extensive obliterative changes are associated with elevated pulmonary arteries pressure, pulmonary vascular resistance, and right ventricular (RV) dysfunction, resulting in vascular fibrosis and stiffening [108,109]. Mounting evidence has shown that treatment with rat MSC or human MSC treatment is able to decrease pulmonary vascular resistance, improve vascular endothelial function and right ventricular function in the monocrotaline or Su5416/hypoxia-injured lung [110][111][112][113] through regulating [Ca 2+ ]i signal-associated cellular behaviours [114], normalizing the expression levels of apoptosis (active-caspase-3), cellular proliferation (p-38 MAPK and ERK5), and inflammation markers (TNF-α, IL-1β, IL-6) [115], suppressing TLR-4 signalling [116], expressing Heme Oxygenase-1 (HO-1), enhancing let-7a expression [117], and dampening endothelialmesenchymal transition (EndMT) [118,119]. Moreover, high throughput sequencing has demonstrated that six miRNAs of MSCs (upregulated: miR573 and miR1246; downregulated: miR206, miR-133a-3p, miR-141-3p and miR-200a-3p) are differentially expressed with co-culturing with human pulmonary arterial endothelial cells (HPAECs) [120].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a chronic and devastating disease in which extensive obliterative changes are associated with elevated pulmonary arteries pressure, pulmonary vascular resistance, and right ventricular (RV) dysfunction, resulting in vascular fibrosis and stiffening [108,109]. Mounting evidence has shown that treatment with rat MSC or human MSC treatment is able to decrease pulmonary vascular resistance, improve vascular endothelial function and right ventricular function in the monocrotaline or Su5416/hypoxia-injured lung [110][111][112][113] through regulating [Ca 2+ ]i signal-associated cellular behaviours [114], normalizing the expression levels of apoptosis (active-caspase-3), cellular proliferation (p-38 MAPK and ERK5), and inflammation markers (TNF-α, IL-1β, IL-6) [115], suppressing TLR-4 signalling [116], expressing Heme Oxygenase-1 (HO-1), enhancing let-7a expression [117], and dampening endothelialmesenchymal transition (EndMT) [118,119]. Moreover, high throughput sequencing has demonstrated that six miRNAs of MSCs (upregulated: miR573 and miR1246; downregulated: miR206, miR-133a-3p, miR-141-3p and miR-200a-3p) are differentially expressed with co-culturing with human pulmonary arterial endothelial cells (HPAECs) [120].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“… 34 , 35 Over the past few decades, MSCs, regarded as “the next pillar of medicine” have been shown to successfully reduce inflammatory response and collagen deposition, 36 reduce pulmonary vascular resistance, and improve vascular endothelial function and appropriate ventricular function in a bleomycin-induced model of lung injury. 37 , 38 Recent studies support the utility of MSC therapy as a potential option for treating cases of severe ARDS and cytokine storm resulting from the novel coronavirus disease COVID-19, although preclinical data are current lacking. 39 However, existing data suggests that only a small number of MSCs are capable of preferentially targeting damaged regions and surviving for over 24 h following systematic administration.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to address that hMSCs can persist long-term in the RV by intracoronary injection and are a potential cell source for tissue repair in RV dysfunction induced in a large animal model of pulmonary hypertension (Badr Eslam et al, 2017). Herein, we expanded these beneficial findings on hMSCs for the whole cardiopulmonary system, now in a suitable rodent model of PAH.…”
Section: Discussionmentioning
confidence: 99%